PENGARUH ROTASI DAN MUTASI KERJA TERHADAP KINERJA KARYAWAN PT. ONAMBA INDONESIA KARAWANG - Dewi Hudiyah; Erliany Syaodih (Program Magister Manajemen Universitas Adhirajasa Reswara Sanjaya, 2022)
Employee performance at PT. Onamba Indonesia-Karawang. The population used in this this study were employees of PT. Onamba Indonesia-Karawang as 300 employees. The sample in this study were 33 respondents. The type of data in this study is primary. Methods of data collection through interviews and questionnaires. The research method used is quantitative method. The results of the study prove partially positive and significant towards employee performance. Job mutations have a positive and significant effect on employee performance partially and work rotation and job mutations jointly affect employee performance